2016
DOI: 10.1002/oa.2519
|View full text |Cite
|
Sign up to set email alerts
|

Mother City and Colony: Bioarchaeological Evidence of Stress and Impacts of Corinthian Colonisation at Apollonia, Albania

Abstract: This study uses bioarchaeological methods and interpretive frameworks, in conjunction with archaeological and textual evidence, to document and interpret the record of Greek colonial interactions between Corinth and local populations at Apollonia, Albania, in the region known as Illyria (modern Albania). A series of Illyrian human remains (n = 304; Early Iron Age–Hellenistic periods) and Corinthian human remains (n = 72; Neolithic–Hellenistic periods) were examined for evidence of physiological stress in order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Another possible explanation for the pattern we observed is that the city of Himera may have experienced greater stress than other parts of the Greek world (from which the 480 BCE soldiers came), which would explain why citizens and probable citizen‐soldiers (i.e., 409 BCE soldiers) of Himera show greater evidence of stress than the probable foreign‐born 480 BCE soldiers. This explanation is not well supported by the literature, as prevalence of skeletal pathology documented at Himera is similar to the prevalence of pathology reported in other parts of the Greek world (Keenleyside and Panayotova, ; Kyle et al, ). Colonized and marginalized people were common throughout the Greek world, especially in Greek colonies (Zuchtriegel, ).…”
Section: Discussionmentioning
confidence: 71%
“…Another possible explanation for the pattern we observed is that the city of Himera may have experienced greater stress than other parts of the Greek world (from which the 480 BCE soldiers came), which would explain why citizens and probable citizen‐soldiers (i.e., 409 BCE soldiers) of Himera show greater evidence of stress than the probable foreign‐born 480 BCE soldiers. This explanation is not well supported by the literature, as prevalence of skeletal pathology documented at Himera is similar to the prevalence of pathology reported in other parts of the Greek world (Keenleyside and Panayotova, ; Kyle et al, ). Colonized and marginalized people were common throughout the Greek world, especially in Greek colonies (Zuchtriegel, ).…”
Section: Discussionmentioning
confidence: 71%
“…infra) with physiological repercussions. Though covering a different region, a statistical comparison of pre-and post-colonial skeletal remains by Kyle et al (2016) revealed the physical stigmata of the stresses inflicted upon the population of Apollonia (in present-day Albania) after the Greek colonization in the sixth century BC. The authors attribute this physiological stress to a reduction in locally available resources and the adverse health impact of urbanization (insalubrity and propagation of disease).…”
Section: A Migrant Population With a Skewed Sex Ratiomentioning
confidence: 99%
“…A number of recent bioarchaeological studies on Archaic to Roman era material in Greece have followed Perry's () recommendation and combined bioarchaeological parameters with historical and archaeological data. Notable in this direction is the work by Kyle, Schepartz, and Larsen (), which focused on stress levels in Illyria after its colonisation by Corinthians, McIlvaine, Schepartz, Larsen, and Sciulli (), which explored the relationship between founder cities and colonies by focusing on gene flow between Corinth and its colony in Apollonia, as well as Lagia (), which investigated the economic and social history of Athens from the Classical period until Imperial Roman times.…”
Section: Introductionmentioning
confidence: 99%